A Deep Morphological Characterization and Comparison of Different Dental Restorative Materials. (29th June 2017) - Condò, R.; Cerroni, L.; Pasquantonio, G.; Mancini, M.; Pecora, A.; Convertino, A.; Mussi, V.; Rinaldi, A.; Maiolo, L.
Abstract : Giomer is a relatively new class of restorative material with aesthetics, handling and physical properties of composite resins, and benefits of glass ionomers: high radiopacity, antiplaque effect, fluoride release, and recharge. To verify the superior properties of Giomers, in this study, a deep morphological characterization has been performed with an in vitro comparative study among a Giomer (Beautifil® II by Shofu Dental Corporation, Osaka, Japan), a Compomer (Dyract Extra by Dentsply, Caulk, Germany), glass ionomer cement (Ketac fil plus by 3M ESPE), and a composite resin (Tetric Evoceram by Ivoclar). In particular, mechanical and optical properties and ageing effects have been compared to investigate materials similarities and differences. Indentation tests, UV-Visible spectroscopy, Raman spectroscopy, and weight loss after storage in saliva or sugary drink have been carried out to analyze materials behavior in real conditions. The results confirm the high quality of Giomer material and indicate possible improvements in their usage.